Retrograde incision from orifice (RIO) technique for endoscopic incision of ureterocele: 15 years of outcomes. Issue 1 (February 2023) - Corona, Lauren E.; Lai, Andrew; Meyer, Theresa; Rosoklija, Ilina; Berkowitz, Rachel; Liu, Dennis; Maizels, Max; Cheng, Earl Y.; Lindgren, Bruce W.; Chu, David I.; Johnson, Emilie K.; Gong, Edward M.
Summary: Introduction: Management of obstructing ureterocele often includes endoscopic transurethral incision (TUI) that can be challenging secondary to uncertainty in anatomic landmarks with risk of serious complications. To this end, we innovated a technique using predictable landmarks that begins endoscopic incision at the ureterocele orifice and extends retrograde proximal to the bladder neck (Figure). Objective: With over 15 years of experience in performing this retrograde incision from orifice (RIO) technique, we aimed to examine post-operative outcomes and risk of surgical failure after RIO compared to traditional TUI techniques for ureteroceles. We hypothesized that clinical outcomes after RIO would be superior to traditional endoscopic approaches to decompression of obstructing ureterocele in infants. Study design: A retrospective study of patients ≤12 months old who underwent TUI ureterocele at our institution between 2007 and -2021 was conducted. Pre-, intra- and post-operative characteristics were compared between patients who underwent RIO vs non-RIO TUI. Primary outcome was post-incision febrile urinary tract infection (fUTI). Secondary outcome was a composite failure measure of fUTI, secondary surgery, de novo bladder outlet obstruction, or vesicoureteral reflux. Multivariable Cox proportional hazard models were fitted to compare the time-to-event risk of primary and secondary outcomes between groups. Results: Ninety patients with 92 ureteroceles were included (49 RIO, 43 non-RIO). Median follow-up from TUI was 33 months. RIO had a shorter median operative duration (27 vs 35 min, p = 0.021). Primary and secondary outcomes were similar between groups (fUTI: 29% RIO vs 19% non-RIO, p = 0.27; composite failure 54% RIO vs 69% non-RIO, p = 0.15). In multivariable Cox proportional hazard models, there was no significant difference in risk of fUTI (RIO aHR 0.98, 95% CI 0.38–2.54, p = 0.97) or composite failure (RIO aHR 0.80, 95% CI 0.45–1.44, p = 0.46) between TUI techniques. Discussion: RIO technique for TUI ureterocele is attractive in that it uses predictable anatomic landmarks making it simple to perform. In analyzing this 15-year institutional experience of TUI ureterocele, RIO showed similar success to non-RIO endoscopic incisions. This study is a retrospective, non-randomized, single-institutional study over 15 years and is therefore subject to change in surgeon practice over time and variable practices between providers. Conclusions: Given comparable success and durability over time to other TUI ureterocele techniques, and with the advantage of operator ease using consistent anatomic landmarks, RIO is a worthy option for endoscopic ureterocele decompression. Summary Fig. Retrograde incision from orifice (RIO) technique for endoscopic ureterocele-otomy. a. Diagram depiction of ectopic urethral ureterocele with orifice (exaggerated) b. Identification of predictable anatomic landmarks: orifice is visualized in urethra c. Orifice is engaged by peg electrode and roof of ureterocele is cut in a retrograde fashion via multiple short incisions until just proximal to the bladder neck, opening the obstructing segment to promote upper tract drainage. Summary Figure